PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV DI SDN 014 PUTAT KECAMATAN TANAH PUTIH - Daud, Damanhuri Daud Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstact: This research was motivated by the low science learning outcomes of students with an average grade 54.73% while the value of Minimum Criteria for completeness (KKM) IPA Among the 70 students who numbered as many as 19 people only 4 students who achieve KKM with classical completeness 21.05 % .Penelitian is classroom Action Research (CAR) conducted aiming to improve science learning outcomes SDN 014 fourth grade students with a Implement method Putat TGT. Formulation of the problem is the implementation of inquiry learning model to improve learning outcomes Fourth grade students in science subjects SDN 014 Putat White Land District of Rokan Hilir. This study was conducted on March 10, 2014 Up to 24 April 2014 subjects were fourth graders were 19 students consisting of 12 boys and 7 girls. The parameters measured were the result of student learning, mastery learning, student learning activities and teacher activities. Teacher activity during the learning process by using the application of models of inquiry in the first cycle the first meeting of 66.6% with enough categories, the first meeting of the second cycle of 75% with both categories. Increased 8.4%. At the first meeting of the second cycle of 87.5% with a very good category, silus II II 95.8% meeting the very good category. Increased 8.3%. Activities of students during the learning process by using the application of the inquiry in the first cycle the first meeting of 66.6% with enough categories, the first meeting of the second cycle of 75% with both categories. Increased 8.4%. At the first meeting of the second cycle of 87.5% with a very good category. In the second cycle the second meeting of 95.8% with excellent category increased 8.3%. Application of the model of inquiry in the learning process can improve students' science learning outcomes of basic score (21.5%) to UH I (52.63%), basic score (21.5%) to UH II (72.68%) had increased amounted to 51.18%. The results of the study in the classroom SDN 014 Putat prove that the application of inquiry learning model to improve learning outcomes 014 fourth grade students of SDN Putat Kecatan White Land Rokan Hilir 2013/2014. Keyword: Kooperatif type TGT, Hasil belajar IPA